Moralitas di Era Digital: Tinjauan Filsafat tentang Technoethics - Hamdani, Annisa Dwi; Aulia, Erlinda Risa Nur; Listiana, Yhesa Rooselia; Herlambang, Yusuf Tri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The current era of digitalization allows humans to live side by side with technology. However, this technology has two sides that have positive and negative impacts depending on how we use it. The negative impact of technology use is often caused by a lack of awareness of applicable ethics and norms. This is related to the philosophy of technology, namely technoethics or technology ethics, which is a branch of ethics that deals with moral issues arising from the development and use of technology. The aim of this research is to find out how humans use technology. This research uses the literature study method, the subjects of this research are journals, articles, and books. Research data was taken from secondary data such as journals, articles, and books, then analyzed using descriptive analysis methods. From the results of the research carried out, it can be concluded that based on the literature review, Technoethics tries to handle ethical problems that arise from technological developments and ensures that technology is used responsibly and in accordance with ethical values